Evaluation of the breeding practices and population trend of the Fogera cattle breed in Ethiopia - Tesfa, Assemu; Bimerew, Tewodross; Tilahune, Mekonnen; Kassahun, Demelash; Kebede, Adebabaye; Mengesha, Wondimagegn (Frontiers in Animal Science, 2022)
The study was conducted to estimate the population size, herd structure, and breeding objectives of Fogera cattle in Ethiopia. It was carried out in 23 purposively selected kebeles in five districts of three zones bordering Lake Tana. Interviewed farmers were selected based on their livestock ownership. Primary information on the general production system and trends of Fogera cattle was collected from 527 farmers, and a population count included 479 respondents. To differentiate the pure Fogera cattle from the mixed and highland zebu breeds, color photographs of the three breeds were used by each enumerator. Kebele administrators and elders as well as district and zone officials assisted in the operation to identify the true type of Fogera cattle. MS-Excel (2010) and SPSS (version 20) were used to analyze population size and production systems, respectively. The average cattle holding per household was 7.03 ± 0.2 heads. Analysis of multiple responses revealed that the dominant reasons for keeping cattle in the herd were traction power (96.67%), milk (92.76%), and manure (83.95%). More than half of the respondents (64.65%) practiced culling both male and female animals from their herds. Interviewed farmers selected bulls for mating by coat color (56.84%), body conformation (55.08%), and body size (47.46%). They also indicated that they selected the Fogera breed (48.63%), highland zebu (18.16%), and mixed (17.38%) as bulls for mating with their cattle. Based on the respondents’ information, the population trend of the Fogera breed decreases (40%), increases (13%), is stable (6%), and is not known (41%). From the total population estimated, households own the relatively pure Fogera (41%), Fogera–zebu mix (35%), and highland zebu (24%). In this study, the total estimated number of breeding Fogera cattle was 55,646 ± 16,579 heads. It was concluded that the breed has declined and is dealing with genetic deterioration as the population size decreases due to the shift of grazing lands to crop production. As population estimation was performed by morphological features, further research supported by molecular study should be conducted.